2012
DOI: 10.1111/jpc.12027
|View full text |Cite
|
Sign up to set email alerts
|

Infantile hypertrophic pyloric stenosis: Has anything changed?

Abstract: Aim:The study aims to review the contemporary presentation, diagnosis and treatment of children with infantile hypertrophic pyloric stenosis (IHPS) at an Australian paediatric tertiary centre. Methods: A retrospective case review of patients with IHPS presenting to our institution between January 2004 and December 2010 was performed. Results were compared with a previous study evaluating two earlier 6-year series of patients treated between January 1984 and November 1995. Results: Of 362 infants presenting ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 17 publications
5
41
4
2
Order By: Relevance
“…In 1986, Magilner reported 2 cases of this association and reviewed 35 reported cases. Since these reports, less than 20 cases have been reported in literature, we can realize that the delayed diagnostic is common [3,5] . Now, we report our experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1986, Magilner reported 2 cases of this association and reviewed 35 reported cases. Since these reports, less than 20 cases have been reported in literature, we can realize that the delayed diagnostic is common [3,5] . Now, we report our experience.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, infantile HPS is a common paediatric condition with an incidence of 1 in 400 live births [3,5] . This pathology is 30 times more frequent in patients with EA [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high sensitivity and specificity without any risk of ionizing radiation and its ability to demonstrate other intraabdominal pathologies that might co-exist, US has been widely used as an imaging tool for IHPS diagnosis prior to surgery [6,12,13,[23][24][25]. US was also used in the follow-up of the healing process of medically treated IHPS [26] and in monitoring conservatively treated IHPS cases [16].…”
Section: Discussionmentioning
confidence: 99%
“…IHPS should be considered in any vomiting infant [4], though gastroesophageal reflux (GER), pylorospasm, hiatal hernia, and preampullary duodenal stenosis can also manifest with nonbilious vomiting [1]. The use of ultrasonography (US) in the diagnosis of IHPS evidenced an increase over time, compared to earlier periods [4][5][6]. Only in a few studies was the pyloric ratio (PR) evaluated and it was found to be an additional and useful US parameter in the diagnosis of IHPS in infants with different age and weights [7], including premature infants [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many times ultrasound is the only modality necessary, but when additional imaging is needed, ultrasound may be used to plan how to proceed further with a more expensive study that requires sedation. [32][33][34][35][36][37][38][39][40] Clinical Suspicion of Renal Colic: Ultrasound First?…”
Section: Lynn a Fordham MDmentioning
confidence: 99%